Enhancing cold tolerance and quality characteristics of Carica papaya Linn through the application of 1‐methylcyclopropene, Geranium and Lavender oil - Loh, Meng Yi (John Wiley and Sons, 2024)
SummaryPostharvest application of 1‐methylcyclopropene (1‐MCP), lavender oil (LO) and geranium oil (GO) was investigated in alleviating chilling injury (CI) by regulating the cold tolerance of papaya cold stored at 4 °C for 16 days. The papaya was assessed on the attributes of CI, weight loss, firmness, colour, respiration rate, total soluble solids (TSS), soluble sugar (SS), proline and malondialdehyde content. The antagonistic effect of 1‐MCP against ethylene proved highly effective in delaying fruit ripening and metabolic processes. Notably, a 1‐h misting treatment with 600 mg L−1 1‐MCP (active ingredient, a.i.) solution significantly enhanced papaya's resistance to chilling conditions and reported a remarkable 2.08‐fold reduction in CI damage compared to the control. Furthermore, 1‐MCP‐treated papayas exhibited the highest proline concentration (61.59 μg/g FW) and the lowest malondialdehyde content (39.65 μmol/g FW). Additionally, 1‐MCP‐treated papayas displayed a 1.1‐fold reduction in oxygen consumption compared to the control. They also exhibited minimal changes in weight loss (3.6%), the least increase in TSS and SS compared to the control and better retention of fruit colour and firmness. Comparatively, GO known for its robust antioxidant and antimicrobial properties played a pivotal role in enhancing papaya's cold tolerance and providing superior protection against chilling‐induced damage when compared to the control.